New Aspects of National Security Startegy - V. I. Mizin (Vestnik MGIMO-Universiteta, 2012)
The article describes new aspects in the development of contemporary international security situation and strategic stability. The author opines that the current phase of international relations tends to be rather chaotic and highly unpredictable in its evolution. He attempts to trace the influence of such unorthodox factors as polycentrical nature of the world, departure from exacerbated military confrontation, global terrorist threat on the formation of a principally novel model of strategic stability which substitutes the paradigms of the cold war era. The article dresses the list of specific proposals on the strengthening of military and political security worldwide.